PENELUSURAN SEJARAH, FILOSOFI DAN BUDAYA MAKAN KUE GEPLAK KHAS BETAWI - Kezia Elsty; Zayyini Nahdlah (Jurnal Pariwisata Pesona, 2020)
DKI Jakarta is the capital city of Indonesia for decades. This city becomes melting points for many cultures resulting in the development of the existing culture and food. One of the ethnicities who stay in DKI Jakarta for a long time ago is Betawi. Betawi ethnicities influence DKI Jakarta in various ways and one of them is food. Betawi also rich in a variety of food both savory and sweets. Geplak cake is one of the examples of a traditional sweets cake originated from Betawi made from toasted rice flour in a traditional way called sangrai. This research aim is to get an insight into the history, philosophy, and eating culture of Geplak cake as one of Betawi traditional cake completed with documentation of the authentic method in producing this cake. The descriptive qualitative approached used to analyze the data and information related to Geplak cake as Betawi traditional cake. The data and information are from the interviewees such as Betawi cultural practitioner and Geplak cake makers and sellers located in the DKI Jakarta region. Betawi Geplak cake appeared around the 1900s. There are several explanations of this cake existence such as the availability of the ingredients in an ecosystem, the creativity of ancestors, and the presence of this cake in Betawi cultural ceremony and important occasions. Geplak cake made from rice flour symbolizes prosperity and as the bridge of hospitality among the Betawi people. Geplak cake appears in important events such as engagement, wedding, and Eid al-Fitr. Eating Geplak cake, it is not only a matter of eating this cake as the food but also appreciates the value behind the cake known from history, philosophy, and eating culture. The presence of behind a story about the food itself will give value-added to the food and also be an attractive tourism product as well for representing certain tourism destination. Geplak cake as Betawi traditional cake needs to be preserved as a valuable cultural asset of DKI Jakarta because its existence enriches the whole story of DKI Jakarta.